Bakom stadens kulisser Genus och gränser i Stockholm 1800 - 2000 - Carlsson, Karin; Lennartsson, Rebecka (Kriterium, 2021)
In this book, researchers from different disciplines take the reader on a stroll among forgotten, hidden and exposed rooms in 19th and 20th century's Stockholm. Confectioneries and kitchen entrances, brothels, shop windows and urinal tell of a lost city where boundaries between male and female, public and private, dirty and clean are both sharpened and challenged.